Children of the wild : a novel - Powers, Kevin (Harper, 2026)
"Ewer's Rock, Virginia, 1917. Roy Young is restless, eager to leave this isolated rural valley for university and return with the technical knowledge to modernize his family's farm and bring them properly into the twentieth century. Samantha Hatton, the minister's daughter and Roy's best friend since childhood, knows that both Roy and the town expect them to marry. But Samantha, a daring and ambitious young woman, hungers for more. Above them on the mountain, tending to a lost herd of cattle, is silent Ennis Duke, the mysterious wild boy whose arrival in the valley will upend Ewer's Rock's understanding of itself and its place in the world. Within a year, the lives of these three young people will be dramatically transformed. America has joined the Great War, and Roy and Ennis feel duty-bound to join the fight. In the crucible of conflict, thousands of miles from the familiarity of home, the two men forge a fierce bond. Meanwhile, back in Virginia, Samantha's love and courage endure unthinkable sacrifice in a corner of the world fractured by violence. With the spare and exquisite prose and the profound insight that made The Yellow Birds a landmark work of American fiction, Kevin Powers illuminates the savage, complex, and timeless bonds of loyalty, honor, and heroism. Children of the Wild captures what it means to be human in times of loss--and how, even in darkness, the light of friendship and love endures."--